Pengembangan Modul Elektronik Fisika Berbasis Saintifik menggunakan Software Sigil pada Materi Fluida Statis - Anisah Salma Pigi Taqiyyah; Rini Budiharti; Pujayanto Pujayanto (Universitas Sebelas Maret, 2023)
This study aims to (1) explain the stages of scientific-based electronic module development using Sigil Software on Static Fluid Material with good criteria, and (2) explain the specifications of the electronic module being developed. This study uses the ADDIE development method which consists of three stages, analysis, design, and development. The data obtained is in the form of qualitative data supported by quantitative data sourced from questionnaires. The data sources consisted of 2 experts, 3 physics teachers, and students. The students consisted of 3 students in the one-to-one trial, 9 students in the small group trial, and 90 students in the field trial. The data analysis technique used is qualitative analysis and quantitative analysis. The conclusions from this study are: (1) The electronic module development stage includes: (a) the preparation stage by compiling the material and determining the application to be used, (b) the electronic module manufacturing stage using the main software, namely Sigil and other supporting applications, (c ) the completion stage is validating the electronic module to experts and revising according to suggestions and input from experts, (d) testing the electronic module to students and making revisions according to suggestions and input from students then publishing the file in the form of a Google Drive link. (2) The developed electronic module presents Static Fluid material. Each sub-material is complemented by student activities, learning video content, materials, sample questions and evaluations, and their discussion. There is also a final evaluation at the very end of the module which includes all learning indicators. The final result of this development research is to obtain a scientific-based electronic module using sigil software on static fluid material that meets the criteria very well and is suitable for use.